TWO DIMENSIONAL CHROMATOGRAPHIC ANALYSIS AS A QUALITY MEASURE OF HERBAL EXTRACTS – SALVIA OFFICINALIS - Scheepmaker, Mandé Michelle; Gower, Neil Travis (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Homoeopathic mother tinctures and herbal extracts are used worldwide for medicinal purposes on the basis that the plant extract contains the active components essential for medicinal use. Quality analysis of samples ensures that the correct active components are present for medicinal use. Thin layer chromatography has been used extensively to determine the quality of plant extracts and could just as readily be applied to the assessment of quality of homoeopathic mother tinctures. The development of a multidimensional technique allows for greater quality analyses of these extracts. Materials and Methods: The Salvia officinalis sample was extracted and the one dimensional thin layer chromatographic plate development of extracted sample was performed according to the German Homoeopathic Pharmacopoeia (GHP). Before the two dimensional thin layer chromatographic plates where run, different solvent systems were tested through a comparison of the resultant one dimensional thin layer chromatographic plates with that of the plate developed according to the GHP. The two dimensional thin layer chromatographic plate was developed in one direction using the eluent given in the GHP, the plate was then rotated 90 degrees and further developed using neat dichloromethane. Results and Conclusion: The two dimensional thin layer chromatogram for the selected sample Salvia officinalis was successfully established. This results in a more extensive profile regarding the identification of the individual components present in the homoeopathic mother tincture. The further production of two dimensional chromatograms is essential to the expanded detailed analysis of individual products and potential raw material production of even higher standards.